Murder Kingdom / written by Fred Van Lente; art by Chris Panda; lettered by Becca Carey; edited by James B. Emmett and Lauren Hitzhusen. - Van Lente, Fred (Mad Cave Studios, 2025)
"You must be this tall ... to DIE! Tanith and her best friend are trapped overnight in a fantasy-themed amusement park where someone is killing the employees in the gruesome fashion of the original fairy tales! They have to unravel the mystery before they become the next victims and live never ever after ... Once upon a time, in a strange land called Florida, a masked psycho starts murdering cast members of the Storybook Kingdom theme park in ways identical to the gory original Grimms' Fairy Tales. Princess-turned-detective Tanith is the only person who can unmask the killer before she and her friends are all Dying Unhappily Never After! Toon-themed terror from six-time New York Times bestselling writer Fred (Marvel Zombies) Van Lente, artist Chris Panda (Chocklit Shoppe of Horrors: Night Shift, Rom First Strike), and letterer Becca Carey(Radiant Black, Golden Rage)." --